Evolution and effectiveness of bilateral and multilateral development assistance for health: a mixed-methods review of trends and strategic shifts (1990–2022) - Yan Luo; Ying Chen; Beibei Yuan; Ming Xu; Shuduo Zhou; Zhijie Zheng; Siwei Xie; Sijin Du; Yuxin Huang (BMJ Global Health)
Background Development assistance for health (DAH) plays a vital role in supporting health programmes in low- and middle-income countries. While DAH has historically focused on infectious diseases and maternal and child health, there is a lack of comprehensive analysis of DAH trends, strategic shifts and their impact on health systems and outcomes. This study aims to provide a comprehensive review of DAH from 1990 to 2022, examining its evolution and funding allocation shifts.Methods We conducted a mixed-methods review, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic literature search was performed across PubMed, Embase, Web of Science and the Cochrane databases, yielding 102 eligible studies. Quantitative data were obtained from the Institute for Health Metrics and Evaluation database, covering DAH data from 1990 to 2022. Qualitative data were analysed through thematic synthesis based on the WHO’s six health system building blocks.Results The DAH has predominantly focused on HIV/AIDS and maternal and child health. Despite the increasing global burden of non-communicable diseases (NCDs), the proportion of DAH allocated to NCDs remained low, increasing only from 1% in 1990 to 2% in 2022. Similarly, the overall funding for health system strengthening decreased from 19% in 1990 to 7% in 2022. Major contributors to DAH included the USA, the UK and the Bill & Melinda Gates Foundation. While associations between DAH and improvements in certain health outcomes were observed, establishing causality is challenging due to multiple influencing factors. The COVID-19 pandemic underscored the importance of robust health systems. However, DAH allocation did not show any substantial shift towards health system strengthening during this period. Economic evaluations calculated the median incremental cost-effectiveness ratio of DAH interventions,Conclusions This study reviews DAH trends from 1990 to 2022, showing a predominant focus on HIV/AIDS and maternal and child health, with insufficient attention to NCDs and health system strengthening. Despite the increasing burden of NCDs and the impact of COVID-19, DAH priorities have not significantly shifted, highlighting the need for ongoing evaluation and strategic adjustments. To enhance DAH effectiveness, it is crucial to adopt a more balanced approach and also align interventions with needs from recipient countries and implement evidence-based strategies with continuous monitoring and evaluation.